Immediate and late follow-up results of auto- and alloplastic operations in inguinal hernias - Z. T. Shirinov; E. A. Alieva; Z. N. Azadova; N. Kh. Khankishiev (Клінічна хірургія, 2020)
Objective. To conduct a scientific investigation for comparative investigation of results of auto- and allohernioplastic operations.